Rome in London: Richard Du Bourg, Cork Modelling, and the Virtual Grand Tour - Arnott-Davies, Rees (Romanticism on the Net)

(untitled) (Université de Montréal, 2018)
Richard Du Bourg (1738-1826) is a neglected figure in accounts of British antiquarian museum culture. However, for nearly fifty year his ‘museum’, located in exhibition spaces across London, was a key site for public engagement with classical antiquity. Du Bourg’s relief models in cork of Roman, Greek and British monuments and ruins attracted a heterogeneous audience including nobility, merchants, architects, artisans and children. This article focuses on the final iteration of the museum at Lower Grosvenor Street between 1802 and its sale at auction in 1819; shedding new light on the innovative modes of representation and display that were incorporated by Du Bourg into his modelling and exhibition practice, and the forms of sociability fostered by such modes. With a focus on the single surviving illustration of the museum, this article carefully unpacks the layers of historical and cultural meaning sedimented in such two-dimensional images, contributing to methodological debates on the writing of cultural histories through images of and from the past.